Agribusiness management in India: A review-based approach and future agenda - Mohammad, Suleiman Ibrahim Shelash; Karthikeyan, Poornima; Raja, N.; Muthukrishnan, K. Binith; Vasudevan, Asokan (International Journal of Innovative Research and Scientific Studies, 2025)
This study is a review-based approach that examines agribusiness management in India during this era of disruptive innovation and over recent years. Utilizing the advanced search option available in the Scopus database, relevant scholarly articles are fetched using keywords such as "agri-business management," "agriculture business management," "agricultural management," "agribusiness," "Agritech," and "farm management" in the context of India. The study aimed to find the key themes, trends, and gaps in the existing literature. Through an SLR, the researchers explore the advancements in agribusiness practices, technological innovations, and market dynamics in the agribusiness sector in India. Using the PRISMA framework, papers were filtered systematically, and only relevant papers were included for the study. A total of 74 papers were included in the study. Using Python libraries, topic modeling was performed, and the papers were clustered according to the themes. Five themes were discussed along with the synthesis of a few selected papers. The findings of the study would be very useful to the institutes teaching agribusiness management and for practitioners to guide the sector in the right direction. A few best practices from other countries were discussed in this article to provide a global perspective.